Kinerja Inspektorat Daerah dalam Pelaksanaan Pengawasan Laporan Keuangan Pemerintah Daerah (LKPD) Kota Denpasar Tahun 2018 - Kusuma Dewi, Made Dharmayanthi; astra Wijaya, Komang Adi S; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2020)
ABSTRACT This study aims to determine the performance of the Regional Inspectorate regarding the Implementation of Supervision Regional Government Financial Statement in Kota Denpasar on 2018. This research was conducted in Denpasar City with informants consisting of Inspectorate employee, and several Dinas supervised by the Denpasar City Inspectorate namely the Dinas Pendidikan, Dinas Kesehatan and Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu. The research method using in this research is descriptive qualitative. The results showed that the supervision carried out by the Denpasar City Inspectorate through three stages, namely: First, preliminary control which is an oversight before the activity takes place, secondly cocurrent control which is an oversight carried out during the activity, the third is feedback control that is supervision carried out after the activity takes place. The performance indicators that influence the implementation of financial audit supervision are: 1) Input indicators, 2) Process Indicators dan 3) Results Indicators. Keywords: Performance, Denpasar City Inspectorate, Supervision Process, Local Government